Competency-Based Education Programs in Texas An Innovative Approach to Higher Education - Daugherty, Lindsay (RAND Corporation, 2015)
This report assesses the Texas experience in the context of national competency-based higher-education movement. Competency-based education in Texas is examined through six institutions that currently offer these programs and recent state efforts to support them. The approach included review of relevant documents, webpages, and interviews with program administrators, a sample of students enrolled in one of the programs, and a state policymaker.